2018
DOI: 10.1111/jre.12608
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics alter the immune response of gingival epithelial cells challenged by Porphyromonas gingivalis

Abstract: Background and Objective Although previous studies revealed the potential use of probiotics in the control of periodontitis, little is known about their interactions with gingival epithelial cells (GECs). Since GECs comprise the first defense in the subgingival microenvironment, the aim of this study was to evaluate the effect of probiotic lactobacilli and bifidobacteria strains on OBA‐9 cells challenged with Porphyromonas gingivalis. Methods Immortalized human GECs (OBA‐9) were challenged with live P. gingiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
0
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(76 citation statements)
references
References 57 publications
2
62
0
12
Order By: Relevance
“…Moreover, FIMA is associated with pathogen adhesion/invasion to epithelial cells [44] and it is recognition by host cells through TLR2 and TLR4 receptors with downstream activation of pro-inflammatory cytokines [45]. Thus, fimA down-regulation may explain our previous study that found a modulation of the immune response triggered in gingival epithelial cells followed by a reduction in the adhesion of P. gingivalis ATCC 33277 [9]. Curiously, all tested probiotics supernatants were able to down-regulate the expression of mfa1 in multi-species biofilm assays.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…Moreover, FIMA is associated with pathogen adhesion/invasion to epithelial cells [44] and it is recognition by host cells through TLR2 and TLR4 receptors with downstream activation of pro-inflammatory cytokines [45]. Thus, fimA down-regulation may explain our previous study that found a modulation of the immune response triggered in gingival epithelial cells followed by a reduction in the adhesion of P. gingivalis ATCC 33277 [9]. Curiously, all tested probiotics supernatants were able to down-regulate the expression of mfa1 in multi-species biofilm assays.…”
Section: Discussionmentioning
confidence: 89%
“…Virulence of P. gingivalis is mediated by an array of factors involved in several functions, such as attachment to host surfaces and other oral microorganisms, acquisition of nutrients, induction of a destructive inflammatory response and evasion of host response. Probiotics were not only able to decrease the abundance of P. gingivalis in multispecies biofilms but were also able to inhibit adhesion and invasion of P. gingivalis to GECs [9]. Once again, these activities were dependent on the P. gingivalis strain, since the tested lactobacilli were able to inhibit P. gingivalis W83 adhesion to but not the invasion of GECs, whereas both adhesion and invasion of ATCC 33277 were inhibited.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations